التَّفكير العلمي عند يونس بن حبيب البصريِّ - خضير حسين علي (Journal of College of Education, 2019)
This research, through the vocabulary of scientific thinking, attempted to provide a systematic and objective approach to the scientific thinking of the Arabs and in a strong linguistic environment in the city of Basra by highlighting the knowledge of the founding flags of the integrated intellectual system in linguistics, Which made him a resource for many of the contemporary scholars of his and the Tallinn for his time, and they return to him in many issues of the theoretical and applied language. The research revealed the foundations of scientific thinking in Yunus bin Habib Basri; those pillars that rely on the scientific method of careful reflection and full extrapolation and objectivity and mechanisms of experimentation, and methods of thinking, and critical sense of insight, and others. He was an approach to independence from the foundations of his visual school, and he took great care of the intellectual problems in people’s minds.